2019
DOI: 10.3389/fonc.2019.01068
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Ki-67 in Patients With Resected Triple-Negative Breast Cancer: A Meta-Analysis

Abstract: Background: Ki-67 is a widely used marker of tumor proliferation, but the prognostic value of ki-67 in triple-negative breast cancer (TNBC) has not been comprehensively reviewed. This meta-analysis was conducted to evaluate the association between ki-67 expression and survival of patients with resected TNBC.Materials and Methods: Relevant studies, evaluating the prognostic impact of pretreatment ki-67 in resected TNBC patients, were identified from PubMed, Embase, Web of Science, China National Knowledge Infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 59 publications
0
34
0
1
Order By: Relevance
“…Ki-67 is a nuclear antigen present in fast proliferating cells that have been widely used in cancer diagnosis. 28 Studies showed a high level of Ki-67 was associated with severity of tumor and poor prognosis in breast cancer and Ki-67 could be used to indicate different prognosis and treatment in TNBC patients. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 is a nuclear antigen present in fast proliferating cells that have been widely used in cancer diagnosis. 28 Studies showed a high level of Ki-67 was associated with severity of tumor and poor prognosis in breast cancer and Ki-67 could be used to indicate different prognosis and treatment in TNBC patients. 29 …”
Section: Discussionmentioning
confidence: 99%
“…The tumor proliferation of breast cancer patients can be reflected by Ki-67 expression (34). Particularly, if the level is ≥14%, the Ki-67 level is positive, and if the level is <14%, the Ki-67 level is negative (35). The Ki-67 marker index is considered an important prognostic marker and a significant indicator of potential triage to chemotherapy (36).…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological grading was based on the Nottingham histological grade [ 21 ]. The Ki-67 labelling index (LI) was considered high when ≥40% of the neoplastic cells were labelled [ 22 ]. Stromal tumour-infiltrating lymphocytes (TILs) were identified using haematoxylin and eosin staining, and were considered lymphocyte-predominant breast cancer (LPBC) at ≥60% and non-LPBC at less than 60%, according to the TIL Working Group recommendation [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%